Histopathological Study of Guided Lung Biopsies - Garima, B; Renuka, I V; Ramya, P; Prasad, Durga; Uppala, Pravallika; ., Prathyusha (Annals of Pathology and Laboratory Medicine, 2020)
Background: Guided lung biopsies and Fine needle aspiration cytologies (FNAC) have been used for diagnosis of peripheral lung lesions and both have advantages and disadvantages. In our institution, core needle biopsies of lung are done from Computed tomography (CT) and thoracoscopic guided procedures. Methods: The histopathological records of our General Hospital were retrospectively reviewed for core needle biopsies of lung lesions between July 2018 to June 2019 (1 year). There were 89 cases during this period. Results: There were a total of 89 cases (66 males and 23 females) during the study period of one year. The specimens received were linear bits and average size was 0.5cm in length. Non-neoplastic lesions were 24(26.9%) and neoplasms contributed to 65 cases (73.03%). Maximum number of cases (47 cases) were reported in the age group of 41-60 years (47 cases) with male preponderance. In all the.age groups, malignant lesions were more common in which Adenocarcinoma was predominant. Conclusion: To conclude, in our study malignancies predominated over non neoplastic lesions. The most common histological cell type encountered in this study was an Adenocarcinoma.